Does IPO prospectus in Malaysia disclose relevant risk?. Issue 4 (26th November 2019) - Ng, Sin Huei; Lee, Chen Suen
Abstract : Purpose: The study intends to shed lights on whether the risk factors disclosed in the initial public offering (IPO) prospectus in Malaysia are able to reflect the actual risks of stocks once they are traded on the exchange. In other words, the purpose of this paper is to explore whether prospective investors will be able to benefit, in terms of the more accurate risk information, from the risk disclosures in the IPO-prospectus. Design/methodology/approach: Using data obtained from 118 IPO prospectuses of Malaysian companies that issued shares on Bursa Malaysia in the period from 2009 to 2016, the authors investigated whether the "risk factor" section in the IPO prospectuses provides sufficient risk-relevant information to investors. To determine whether companies disclose risk-relevant information, a detailed content analysis of the risk sections was carried out to obtain an aggregate measure of risk disclosure. Findings: The findings revealed that the aggregate measures of risk extracted from these texts did not successfully predict the following outcomes: the volatility of companies' future stock prices, the sensitivity of future stock prices to market-wide fluctuations and the severe declines in future stock prices. Practical implications: As indicated by the findings, the authors, therefore, deduce that the IPO prospectuses of Malaysian companies do not provide sufficient risk-relevant information in the risk factor section. The findings imply that overall the management of Malaysian companies would neither be able nor willing to disclose the right and relevant information to the public via IPO prospectus. Originality/value: Many corporate risk disclosure studies focus primarily on the disclosures of annual reports of companies. The study intends to fill the gap by focusing on the risk disclosure in the IPO-prospectus. Risk disclosures in IPO-prospectus are farmore extensive than annual reports and, therefore, provide a richness of information that will not be available in the annual reports.